Research of Peganum harmala: Phytochemical Content, Mineral Profile, Antioxidant, Antidiabetic, Anticholinergic Properties, and Molecular Docking - İzol, Ebubekir; Turhan, Münire; Yapıcı, İsmail; Necip, Adem; Abdullah Yılmaz, Mustafa; Zengin, Gökhan (Chemistry & biodiversity, 2025)
ABSTRACT Peganum harmala is a significant medicinal, aromatic plant used in traditional medicine and the subject of many studies. In this study, the phytochemical compound and mineral profile of the plant's ethanol extract were identified quantitatively. Antioxidant properties were determined by total phenolic and flavonoid content, FRAP, DPPH, CUPRAC, ABTS, metal chelating, and phosphomolybdenum assays. Antidiabetic, anticholinergic, and skin care properties were specified by the inhibition of tyrosinase, α‐glucosidase, α‐amylase, butyrylcholinesterase (BChE), and acetylcholinesterase (AChE) enzymes, respectively. In addition, binding interactions of major phytochemicals with all enzymes were investigated by molecular docking studies. The phytochemical compound of the extract contained significant bioactive components such as acacetin, gentisic acid, p‐coumaric acid, quinic acid, rutin, apigenin, and chrysin, while the mineral profile was rich in salt elements. AChE, BChE, tyrosinase, α‐amylase, and α‐glycosidase enzyme inhibitor results were determined as 2.99 mg GALAE/g, 4.14 mg GALAE/g, 35.8 mg KAE/g, 2.76 mmol ACAE/g, and 1.20 mmol ACAE/g, respectively. As a result, it was identified that it had antioxidant properties and strongly inhibited all enzymes except tyrosinase. The docking scores of major bioactive phytochemicals were found to be high. The best binding pose was obtained by docking acacetin into the active site of AChE (PDB: 4EY7), BChE (PDB: 4BDS), α‐glucosidase (PDB: 3WY1), α‐amylase (PDB: 6GXV) and tyrosinase (PDB: 2Y9X) receptors. Docking score values were calculated as −10.4, −9.2, −8.8, −7.8, and −7.4 kcal/mol, respectively. Thus, it was revealed that P. harmala has an important potential in drug research and treatment of some diseases.